An alternative material model using a generalized ?J2? finite-strain flow plasticity theory with isotropic hardening - Écsi, Ladislav; Élesztős, Pavel (Zielona Góra: Uniwersytet Zielonogórski)
In this paper an alternative material model using a generalized "J2" finite-strain flow plasticity theory with isotropic hardening is presented. The model is based on a new nonlinear continuum mechanical theory of finite deformations of elasto-plastic media which allows for the development of objective and thermodynamically consistent material models.
Keywords: nonlinear continuum theory of finite deformations of elasto-plastic media; generalized "J2" flowplasticity theory with isotropic hardening; objective and thermodynamically consistent formulation